2017
DOI: 10.1371/journal.pone.0177092
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome after abdominal packing for uncontrolled postpartum hemorrhage despite peripartum hysterectomy

Abstract: BackgroundIntra-abdominal packing is a possible option for persistent bleeding following hysterectomy for postpartum hemorrhage. However, to date, only very limited data about maternal outcome after intra-abdominal packing for surgically uncontrolled hemorrhage following hysterectomy are available. The objective of the current study was to estimate maternal outcome after intra-abdominal packing following unsuccessful peripartum hysterectomy for postpartum hemorrhage.MethodsA questionnaire was mailed to all mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Rather, this remains a crucial skill, which complements the other surgical skills essential when managing massive peripartum bleeding as is evidenced by the fact that one in 14 cases in a recent series of 718 peripartum hysterectomies required further packing for intractable bleeding. 9 Lastly, we agree with the authors' comment that accoucheur experience is important when making the decision whether or not to initiate packing; what is equally important is that the clinician resists the temptation to place further sutures when coagulopathy has evolved or where haemorrhage persists from large raw surfaces, venous plexuses and inaccessible areas, as such aggressive surgery is likely to provoke further bleeding.…”
Section: Dear Editorsupporting
confidence: 52%
“…Rather, this remains a crucial skill, which complements the other surgical skills essential when managing massive peripartum bleeding as is evidenced by the fact that one in 14 cases in a recent series of 718 peripartum hysterectomies required further packing for intractable bleeding. 9 Lastly, we agree with the authors' comment that accoucheur experience is important when making the decision whether or not to initiate packing; what is equally important is that the clinician resists the temptation to place further sutures when coagulopathy has evolved or where haemorrhage persists from large raw surfaces, venous plexuses and inaccessible areas, as such aggressive surgery is likely to provoke further bleeding.…”
Section: Dear Editorsupporting
confidence: 52%
“…Thus, mechanical pressure applied to bleeding foci can be increased without having to perform relaparotomy to increase the number of sponges. Deffieux et al ( 15 ) reported the success rate of abdominal packing as 62% in their study. Packing failed in 38% of cases and death occurred in 13 ( 16 ) .…”
Section: Discussionmentioning
confidence: 86%
“…If the sponges are not squeezed sufficiently, bleeding may continue and packing may result in failure. In the study performed by Deffieux et al, ( 15 ) the authors failed to determine the required number of pads in a successful packing treatment. In Karateke packing, the compression strength exerted on the area of bleeding can be increased with the same number of sponges by increasing the traction force and volume of the intra-abdominal balloon.…”
Section: Discussionmentioning
confidence: 99%
“…Deffieux et al evaluated the use of intra-abdominal packing for uncontrollable persistent bleeding after peripartum hysterectomy. They found that abdominal packing, used for duration of 24 to 48 hours, is a good option for patient with life-threatening postpartum bleeding after hysterectomy [ 30 ]. A study conducted at China among patients with MAP with high-intensity focused ultrasound (HIFU) and uterine artery embolization (UAE) for retained placenta accreta [ 31 ].…”
Section: Discussionmentioning
confidence: 99%